Assessment of Engineering and Environmental Risks Associated with Solid Medical Waste Management at Sorman Teaching Hospital (Libyan Journal of Ecological & Environmental Sciences and Technology, 2026)
This study evaluates the operational efficiency and environmental performance of solid medical waste management at Sorman Teaching Hospital in western Libya, with a focus on engineering-related processes including waste segregation at source, internal collection logistics, transportation pathways, temporary storage conditions, and final disposal practices. The study further quantifies daily and weekly waste generation rates as key indicators for assessing environmental and public health risks and for supporting infrastructure and capacity planning. Conducted during the autumn of 2024, the research adopted a descriptive–analytical engineering approach based on systematic field inspections. Data were collected through a validated structured questionnaire supported by direct quantitative measurements and were statistically analyzed using the Statistical Package for the Social Sciences (SPSS). The results indicate that the hospital generates approximately 1,375kg of solid medical waste per week, comprising both hazardous and non-hazardous fractions, which imposes a considerable environmental load and operational challenge on existing waste management infrastructure. Statistical analysis revealed significant interdepartmental variability in waste generation rates (p < 0.05), with the nephrology department accounting for the highest contribution (approximately 45.71% of total waste), while the ophthalmology department exhibited the lowest generation rate. These findings highlight inefficiencies in current waste flow design and resource allocation, as well as the absence of a standardized, performance-based waste management system.From an engineering and environmental science perspective, the study emphasizes the necessity of implementing an integrated solid medical waste management framework that incorporates optimized process design, improved storage and handling facilities, adequate treatment and disposal capacities, and continuous monitoring through key performance indicators (KPIs). Strengthening technical infrastructure, enhancing workforce training, and ensuring strict compliance with environmental regulations and health standards are recommended to reduce environmental risks and improve the overall sustainability of medical waste management systems. The study was limited to a single public hospital and a specific time period. Accordingly, future research is recommended to expand the scope and duration of the study and to include more detailed performance indicators to enhance the efficiency and sustainability of solid medical waste management, covering both hazardous and non-hazardous waste
Keywords: solid waste; medical waste; hazardous waste